Role of hatchery in the fish culture development of Rajshahi district in Bangladesh (University Journal of Zoology, Rajshahi University, 2007)
Key words: hatchery; brood fish; breeding; spawning; fish fry Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 73-76